PENGEMBANGAN MEDIA BLOG TERINTEGRASI SAINS-ISLAM UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI - Endayani Rostika (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The use of technology in the form of integrated science-Islamic blog media in geography learning is the latest step as a solution to improve student learning outcomes. This study aims to determine 1) the feasibility of the product development of science-Islam integrated blog media and 2) increase learning outcomes of Geography after using science-Islam integrated blog media on the distribution of world flora and fauna. This study uses the ADDIE development model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. The product is validated by subject matter experts on geography, media, and science-Islam integration and is limited to teachers and students. The product trial subjects consisted of a small group of 25 students and a large group of 35 students of class XI SMAN 6 Garut. Instruments in the form of a questionnaire to determine the feasibility of integrated science-Islamic blog media and test questions to determine the increase in learning outcomes of Geography. Data were analyzed descriptively. The results showed that: 1) the integrated science-Islamic blog media was appropriate for use in learning with the very good category (feasibility value = 93.77%) and 2) the science-Islam integrated blog media increased learning outcomes in geography with the high category = 34.28% and moderate = 54.29%. Abstrak Pemanfaatan teknologi berupa media blog terintegrasi sains Islam dalam pembelajaran geografi merupakan langkah terbaru sebagai salah satu solusi untuk meningkakan hasil belajar siswa. Penelitian ini bertujuan untuk mengetahui 1) kelayakan produk pengembangan media blog terintegrasi sains-Islam dan 2) peningkatan hasil belajar Geografi setelah menggunakan media blog terintegrasi sains-Islam pada materi Peserbaran Flora dan Fauna Dunia. Penelitian ini menggunakan model pengembangan ADDIE terdiri dari 5 tahap, yaitu analysis, design, development, implementation, dan evaluation. Produk divalidasi oleh ahli materi Geografi, media, dan integrasi sains-Islam serta diujicobakan terbatas kepada guru dan siswa. Subyek uji coba produk terdiri dari kelompok kecil sebanyak 25 siswa dan kelompok besar sebanyak 35 siswa kelas XI SMAN 6 Garut. Instrumen berupa kuesioner untuk mengetahui kelayakan media blog terintegrasi sains-Islam dan soal tes untuk mengetahui peningkatan hasil belajar Geografi. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa: 1) media blog terintegrasi sains-Islam layak digunakan dalam pembelajaran dengan kategori amat baik (nilai kelayakan = 93,77%) dan 2) media blog terintegrasi sains-Islam meningkatkan hasil belajar Geografi dengan kategori tinggi = 34,28% dan sedang = 54,29%.